Assessment of Extractions of Deciduous Mandibular Canine Teeth to Correct Linguoversion Malocclusion in 17 Dogs. (September 2022) - Herrmann, Kirk; Taney, Kendall
A search of medical records at the Center for Veterinary Dentistry and Oral Surgery, Gaithersburg, MD was conducted to identify patients who received extractions of deciduous mandibular canine teeth to treat linguoversion. Patients were included if they were less than 5.5 months of age and had a diagnosis of deciduous class 2 or bilateral class 1 malocclusions. Treatment was considered a success if normocclusion of the permanent dentition was achieved at follow up evaluation. Seventeen patients represented 13 different breeds. No significant correlation was seen between age of treatment (mean age 3.34 months) or sex (11 males, 6 females). Six patients had class 1 malocclusions (35.29%) and eleven patients had class 2 malocclusion (64.71%). Of the six dogs treated for class 1 malocclusions, two had traumatic palatal contact and four had only minor soft tissue contact. Eleven cases of class 2 malocclusion were treated and of these there was one mild, six moderate, and four severe cases of mandibular distocclusion. All cases treated for class 1 malocclusions had a successful outcome resulting in permanent normocclusion (100%), while class 2 malocclusions had success in three of eleven cases (27.27%). The outcomes based on occlusion type were determined to be significant (p = 0.009). All participants had immediate relief of soft tissue trauma and no significant side effects of treatment were recorded. The results show that extractions of deciduous linguoverted mandibular canine teeth (LMC) can immediately improve traumatic impingement and may be a factor in providing a comfortable and functional adult occlusion. Further investigation with a larger sample size would be warranted.